Thymus atrophy and double-positive escape are common features in infectious diseases - Meis, Juliana de (2012)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Pesquisa sobre o Timo. Rio de Janeiro, RJ. Brasil.